Hodotermitidae Optimization Algorithm for Reduction of Real Power Loss - Lenin Kanagasabai (Journal of Telematics and Informatics, 2017)
In this paper, a unique technique, called Hodotermitidae Optimization (HO) algorithm, is utilized for solving reactive power problem. Hodotermitidae Optimization (HO) algorithm is an population based optimization method which is inspired from rational behaviours of Hodotermitidae. The projected Hodotermitidae Optimization (HO) algorithm provides an option making model which is used by Hodotermitidae to adjust their progress trajectories. Hodotermitidae move arbitrarily in the search space, but their trajectories are inclined towards regions with more pheromones. The proposed Hodotermitidae Optimization (HO) algorithm has been tested in standard IEEE 57,118 bus systems and simulation results demonstrate the commendable performance of the projected Hodotermitidae Optimization (HO) algorithm in reducing the real power loss.